Use of heart rate monitors by endurance athletes: lessons from triathletes - O'Toole, M. L.; Douglas, P. L.; Hiller, W. D. (The Journal of Sports Medicine and Physical Fitness, 1998)
Heart rate monitors are commonly used but little is documented about their use. We have reviewed the available literature and supplemented it with data regarding heart rate responses of a large number of highly trained athletes during cycle ergometer and treadmill exercise tests as well as during and following prolonged exercise. The main findings pertinent to the use of heart rate monitors are 1) estimated maximal heart rates are too variable to be of use to precisely guide training pace during cycling or running, 2) during prolonged (> 6 h) cycling or running, a highly trained athlete may expect to exercise at an average intensity close 80% HRmax, but should also expect intensity to decline by 6-7% during the cycle ride or run, and 3) submaximal exercise heart rates following prolonged exercise are not useful for judging completeness of recovery. This information holds the following implications for athletes wishing to optimize use of their heart rate monitors in training and racing: 1) formal maximal exercise tests should be performed to determine true HRmax in each exercise mode, 2) athletes should expect their heart rates to decrease over the course of a long race, and 3) athletes should not assume they completely recovered from a strenuous workout if submaximal exercise heart rates are unchanged. Much remains to be clarified about the heart rate responses of ultraendurance athletes, particularly in relation to performance and the attainment of individual maximal potential.